2022
DOI: 10.33549/physiolres.934871
|View full text |Cite
|
Sign up to set email alerts
|

Potential Protective Effect of Puncture Vine (Tribulus terrestris, L.) Against Xylene Toxicity on Bovine Ovarian Cell Functions

Abstract: The action of the medicinal plant Tribulus terrestris (TT) on bovine ovarian cell functions, as well as the protective potential of TT against xylene (X) action, remain unknown. The aim of the present in vitro study was to elucidate the influence of TT, X and their combination on basic bovine ovarian cell functions. For this purpose, we examined the effect of TT (at doses of 0, 1, 10, and 100 ng/ml), X (at 20 μg/ml) and the combination of TT + X (at these doses) on proliferation, apoptosis and hormone release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The results demonstrated backward restoration without significance in both testosterone and luteinizing hormone secretion with Tribulus terrestris extract (10 mg/kg) after 90 days. A similar influence was researched in Tarko et al (2022) study. They elucidated the effect of Tribulus terrestris alone and in combination with xylene on basic bovine ovarian cell functions in vitro for 48 h. Testosterone release was positively stimulated at a concentration of 100 ng/ml Tribulus extract with xylene compared to the control group, with significance (P < 0.05).…”
Section: Progesterone and Testosterone Secretionsupporting
confidence: 75%
“…The results demonstrated backward restoration without significance in both testosterone and luteinizing hormone secretion with Tribulus terrestris extract (10 mg/kg) after 90 days. A similar influence was researched in Tarko et al (2022) study. They elucidated the effect of Tribulus terrestris alone and in combination with xylene on basic bovine ovarian cell functions in vitro for 48 h. Testosterone release was positively stimulated at a concentration of 100 ng/ml Tribulus extract with xylene compared to the control group, with significance (P < 0.05).…”
Section: Progesterone and Testosterone Secretionsupporting
confidence: 75%
“…Women exposed to aromatic hydrocarbons (e.g., xylene) had reduced levels of luteinizing hormone (LH) [ 6 , 7 ], follicle-stimulating hormone (FSH), and prostaglandin [ 6 ], as well as pregnanediol 3-glucuronide (pd3G) and estrone 3-glucuronide (E13G) [ 7 ]. In vitro studies showed that xylene was able to affect proliferation, apoptosis, and the release of steroids, peptide hormones, and prostaglandins by cultured murine [ 8 ], porcine [ 9 , 10 , 11 ], and bovine [ 12 ] ovarian cells. The adverse effects on the ovary could be due to the ability of xylene to induce oxidative stress and to affect the production and reception of steroid hormones, as well as the intracellular regulators of ovarian cell proliferation and apoptosis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…One such remedy could be the use of functional food—plant products containing flavonoids, which can act as natural adaptogens, antioxidants, and phytoestrogens [ 2 ]. Previously, the abilities of some plants (buckwheat, rooibos, Vitex Agnus cactus [ 11 ]; Tribulus Terrestris [ 12 ]) and plant molecules (quercetin [ 9 ]) to mitigate xylene effects on cultured porcine and bovine ovarian cells have been reported. Nevertheless, the effects of these plant additives have been studied only in the in vitro systems, but these additives were able to prevent only part of the xylene effect.…”
Section: Introductionmentioning
confidence: 99%